Advances in Materials, Mechanical and Industrial Engineering Selected Contributions from the First International Conference on Mechanical Engineering, Jadavpur University, Kolkata, India - Sahoo, Prasanta; Davim, J. Paulo (Lecture Notes on Multidisciplinary Industrial Engineering, 2019)
This book presents selected extended papers from The First International Conference on Mechanical Engineering (INCOM2018), realized at the Jadavpur University, Kolkata, India. The papers focus on diverse areas of mechanical engineering and some innovative trends in mechanical engineering design, industrial practices and mechanical engineering education. Original, significant and visionary papers were selected for this edition, specially on interdisciplinary and emerging areas. All papers were peer-reviewed.